1996
DOI: 10.1063/1.360884
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic anisotropy of Co on Cu(1 1 17)

Abstract: The in-plane magnetic anisotropy of ultra-thin Co films, epitaxially grown on Cu͑1 1 17͒, was determined in situ by means of the magneto-optic Kerr effect down to thicknesses as low as 2 monolayers. Uniaxial and biaxial anisotropy contributions were observed. At room temperature, the uniaxial component is dominant and the easy axis of magnetization is parallel to the step edges. Above 4 monolayers the magnetic anisotropy exhibits a thickness dependence which can be described by volume and interface contributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 25 publications
(28 reference statements)
1
12
0
Order By: Relevance
“…In addition, the separation of the K u in a volume contribution and an interface one is, generally, questionable for a few ML thick films, 40 but also throughout the whole thickness of certain thicker films, as, for instance, in the case of Ni on Cu͑001͒. 41 Another factor which may obscure the linear dependence is the departure of the actual magnetization saturation from the bulk value due to the different film structure and chemical environment in ultrathin films.…”
Section: Magnetic Characterizationmentioning
confidence: 98%
“…In addition, the separation of the K u in a volume contribution and an interface one is, generally, questionable for a few ML thick films, 40 but also throughout the whole thickness of certain thicker films, as, for instance, in the case of Ni on Cu͑001͒. 41 Another factor which may obscure the linear dependence is the departure of the actual magnetization saturation from the bulk value due to the different film structure and chemical environment in ultrathin films.…”
Section: Magnetic Characterizationmentioning
confidence: 98%
“…[8][9][10] In the context of ultrathin-film magnetism, unidirectional Kerr hysteresis loops have been observed for stepped Co surfaces: Co/Cu͑1117͒ films vicinal to fcc ͑001͒ exhibit an unambiguous but unexplained unidirectional shift of order 1 mT. 11,12 Although nonferromagnetic spin structures cannot be ruled out in low-symmetry 3d films, 13 it is not possible to ascribe the observed loops to the well-known exchange between ferromagnetic and antiferromagnetic phases as in Co/CoO.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the unidirectional shift of the hysteresis loops is most pronounced if the field is parallel rather than perpendicular to the steps. 11,12 …”
Section: Co/cu"11n… Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments have been demonstrated that surface induces an in-plane uniaxial magnetic anisotropy in variety of magnetic films grown on SC substrate. [6] As the thickness of layer is reduced, their properties are expected to be strongly influenced by surface and interfaces, which are inevitably rough at atomic scales.…”
Section: Introductionmentioning
confidence: 99%